Régulation internationale et inclusion financière: Entre impasse et renoncements - Christophe Angely (Fondation pour les études et recherches sur le développement international (FERDI), 2023)
– After the great crisis of 2007/2008, the tightening of rules imposed on players in the global financial system aimed to preserve financial stability as a "common good." But this desire to protect the system's integrity was not to be achieved at the expense of greater financial inclusion, so dependent on cross-border payments and more financing for SMEs in developing countries. However, this is precisely what is happening today, and this note explains how these adverse effects have set in. On the one hand, the worrying attrition in the number of correspondent banks, characteristic of "de-risking" or institutional drift in applying AML/CFT rules, contributes to weakening the most vulnerable countries. On the other hand, the difficulty and high cost of collecting financial data condemn local banks to use the "standard" risk analysis model of prudential standards (Bale 3), which relies on the existence of rating agencies, still too few to rate African companies. The international community is finally faced with the need to change these rules, at the risk of seeing them openly circumvented, thus permanently thwarting job creation prospects in countries where SME development is the main driving force. This article explores the options available to players in the system and, more broadly, to the international development community, for whom the development of financial inclusion on the African continent is a vital issue.
Keywords: 330; Banks